Bacterial Pathogens responsible for Urinary Tract Infection Among Patients Attending a Tertiary Hospital in Eastern Nepal - Gupta, Tula Krishna; Timilsina, Bishnu; Rai, Bijendra Kumar; Yadav, Ajay Kumar; Baral, Ratna; Kasaudhan, Smriti Mayur (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: UTI has been more complicated to treat because of the appearance of the pathogen with increasing resistance to antimicrobial agents. It is useful to obtain the local sensitivity pattern in the hospital setting to guide empirical prescription. Methods: This is a prospective hospital-based study to identify the organisms causing UTI and their antibiotic susceptibility. A total of 400 urine samples were collected from the patients attending general OPD of BPKIHS, Dharan, Nepal, having the symptoms of UTI using the purposive sampling technique. We analyzed the midstream, clean catch of the urine and cultured to analyze the bacterial presence. Antibiotics susceptibility was tested using the Kirby-Bauer Disk Diffusion method. The findings were analyzed for the presence of bacteria in different age and sex groups along with their response to different antibiotics commonly used in Nepal. Results: Out of 400 culture samples, 163 (40.7%) showed bacterial growth. Escherichia coli was the most common bacteria (68.7%), followed by Klebsiella spp. (7.4%). Female urine samples showed more bacterial growth compared to males (2.79:1). UTI was common among the young population of the age group (20-29 years). Most of the isolated bacteria were sensitive to Nitrofurantoin (89.7%). Conclusion: UTI commonly occurs both in males and males of all age groups. However, females are more vulnerable to infection. Among many, E. coli is the most prevalent pathogen causing the disease, which is more susceptible to nitrofurantoin. Similarly, this antibiotic is sensitive to the majority of bacteria. Therefore, nitrofurantoin may be the first choice of drug for the population in the Eastern part of Nepal suffering from UTI. Since this study was carried out among a small sample size in one tertiary care hospital, we recommend a bigger study covering a larger population, to further validate the result.